Analysis of the therapeutic effect and influencing factors on unresectable gastric cancer treated with conversion therapy - Han, Saiyi; Han, Shaoliang; Qian, Jun; Guo, Mengfu (Frontiers in Oncology, 2024)
BackgroundGastric cancer (GC) is one of the leading causes of cancer-related death in China, and with the extensive development of conversion therapy, the treatment of advanced unresectable gastric cancer (AUGC) patients has ushered in a new dawn. This study aimed to analyze the efficacy of conversion therapy in AUGC patients and explored the relevant factors affecting the efficacy.MethodWe collected information from GC patients who received conversion therapy from this center and designed a retrospective study.ResultsWe collected relevant clinical data from 160 patients with AUGC. A total of 120 patients who underwent routine R0 resection were identified as conversion cases. A total of 25 patients (15.6%) achieved pCR, 92 patients (57.5%) achieved objective response rate (ORR), 140 patients (87.5%) achieved disease control rate (DCR), and 20 cases (12.5%) observed tumor progression. There were 86 patients who achieved pathological downgrading, with a total downgrading rate of 53.8%. Among the 160 patients, 37 patients (23.1%) had postoperative complications of varying degrees. A total of 72 patients (45.0%) had tumor recurrence/progression at the end of follow-up. The last chemotherapy and surgery (CST) (OR = 1.046, 95% CI 1.013–1.081, p = 0.006), tumor invasion (OR = 32.096, 95% CI 5.091–202.349, p < 0.001), and distant metastasis (OR = 7.050, 95% CI 1.888–26.323, p = 0.004) were independent factors influencing the efficacy of conversion therapy.ConclusionConversion therapy may have a good therapeutic efficacy for AUGC, and some clinical factors affect the efficacy response.